Reusable Visible Light Photoredox Catalysts; Catalyzed Benzylic C(sp3)–H Functionalization/Carbocyclization Reactions - Xia, Jia-Dong; Deng, Guo-Bo; Zhou, Ming-Bo; Liu, Wei; Xie, Peng; Li, Jin-Heng (Synlett, 2012)
The C(sp3)–H functionalization/carbocyclization reaction through the oxidative quenching of visible light photoredox catalysts is established for constructing functionalized 1H-indenes. The process is general for a wide range of benzylic C(sp3)–H bonds and is highly compatible with common functional groups. Importantly, the visible light photoredox catalysts can be recovered and reused at least three times without loss of catalytic activity.
Keywords: photoredox; catalysis; C–H activation; cyclization; alkynes; indenes